Development and validation of the principals’ digital leadership instrument using Rasch measurement model - Yuanyuan, Peng; Alias, Bity Salwana; Mansor, Azlin Norhaini; Hamid, Mohd Rashid Ab (Institute of Advanced Engineering and Science, 2025)
This study addresses the critical need for robust measurement tools in digital leadership (DL) within educational settings—a topic of increasing relevance but limited research. Using the Rasch model measurement analysis, the study aims to develop and validate an instrument tailored to assess principals’ digital leadership (PDL) in China. The questionnaire, based on the five dimensions of the International Society for Technology in Education (ISTE) for education leaders—equity and citizenship advocate (ECA), visionary planner (VP), empowering leader (EL), systems designer (SD), and connected learner (CL)—was adapted to reflect Chinese cultural contexts. Following expert validation, the 33-item instrument was piloted with 188 teachers from higher vocational and technical colleges in Sichuan Province. The Rasch analysis, performed using Winsteps 3.72.3, assessed item fit, unidimensionality, local independence, reliability, separation index, and item-person mapping. The findings revealed that 26 items met all assumptions, demonstrating the strong reliability, validity, and psychometric robustness of the instrument. In conclusion, the validated PDL instrument is a reliable tool for assessing the DL of principals within the Chinese educational context, offering insights into professional development, and sets the stage for future research and policy development in the field of educational leadership.